Upaya Tenaga Pengajar Dalam Meningkatkan Motivasi Baca Al-Qur’an Di Ma’ahad Al-Jami’ah IAIN Curup - Mahfuz; Isabella Isabella; Istikomah Istikomah; Isna Magfiroh; Indah Yumiyanti (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
Reading the Qur'an is an obligation for all human beings who are Muslims, because the Qur'an is the word of Allah or the words of Allah which can be used as a guide for Muslims in the world. But the problem is that at this time many are negligent in that regard, their motivation to read the Koran can be increased with the help of other parties such as Ustadz/Ustadzah. Koran. The research method used to achieve this goal is qualitative research. Data collection was carried out using observation and interview methods. This research aims to examine how the efforts of teaching staff in increasing motivation to read the Koran at Ma'ahad Al-Jamiah IAIN Curup. The results of this study are that the efforts of the teaching staff in increasing motivation to read the Koran at Ma'ahad Al-Jami'ah IAIN Curup have been carried out well as expected. One of the efforts is that in semesters 1-3 one year they are taught about the tahsin and ways to read it, by sending teachers who are experts in the field of tahsin itself. Supporting factors include the sincere intention of reading the Qur'an, strong motivation both externally and internally, and the presence of mentors and educators who teach students to read the Qur'an. Meanwhile, the inhibiting factors for students are impatient in learning to read the Al-Qur'sn and supervisors who are sometimes busy with other duties.